Clinician$1 (Bs Manual on Intra-abdominal Infectionss - Husted, Thomas L.; Wacha, Hannes; Solomkin, Joseph S.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2010)
A clinician's guideline for intra-abdominal infections written by experts in the field. - A manual to help physicians to quickly recognize and better understand the pathogenesis of intra-abdominal infections - Includes several high-quality black and white and color photographs from real-life clinical cases - Adheres to a simple format to serve as essential and quick reference guide for all non-surgical residents and physicians
Assessing and evaluating the patient -- General Management Issues -- Diagnosis and management of specific diseases -- Antimicrobial management.
Keywords: Medicine; Gastroenterology; Surgery; Abdomen -- Surgery; Medicine & Public Health; Abdominal Surgery; Surgery; Gastroenterology; General Surgery